Young Entrepreneurs in Rural Africa: Prevalence, Determinants, Productivity - Paula Nagler; Wim Naudé (Institute for the Study of Labor (IZA), 2014)
Africa is not only the poorest and most rural continent, it is also the most youthful continent in terms of population. Given the large number of young job seekers that will enter the labor market over the next decade, we need a better understanding of rural non-farm entrepreneurship, particularly with regard to the role of young adults in this sector. This paper contributes to the literature by providing empirical evidence on (i) the prevalence of enterprises operated by young adults and the contribution they make to rural household income, the (ii) determinants of enterprise operation, and (iii) labor productivity in enterprises operated by young owners. Using the World Bank's recent LSMS-ISA database that covers six countries in Sub-Saharan African, we find that young adults present a lower share of enterprise owners and derive less income from it. Using a Heckman selection model and panel data analysis, we further find that young household head have a lower likelihood of operating and enterprise and if they operate one, these enterprises are less productive than those of older adults. We conclude that policies to support young entrepreneurs in rural Africa should not only focus on creating conditions that attract young adults to start enterprises, but to also enable young entrepreneurs to improve productivity in already existing enterprises. If these enterprises grow and survive, they can provide a part of the growing number of non-farm jobs that will be needed in Africa's rural areas.
Keywords: J43; L26; M13; O55; O13; Q12; 330; entrepreneurship; labor markets; productivity; rural development; Sub-Saharan Africa; youth employment